Orf – an orphan disease?. (7th July 2015) - Meier, Rahel; Sommacal, Andreas; Stahel, Anina; Grünert, Jörg; Hoffmann, Matthias
Human orf should be considered based on a typical presentation with erythematous papule/nodule to avoid unnecessary over-treatment.